Peningkatan Motivasi Belajar Siswa Kelas IV Melalui Metode Reward And Punishment Pada Mata Pelajaran Pendidikan Agama Islam Di SDN Tambakrejo - Sri Wijayanti; Anggun Wulandari; Waslah Waslah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Education can be said to be an advanced educational institution and get improvements in learning if what is done every day is to receive encouragement in the form of motivation from a teacher to all students. Success in forming a motivational drive for students' learning can be seen from the many changes in each student's daily behavioral activities in participating in learning. This research aims to determine the results of increasing learning motivation for class IV students through the reward and punishment method in Islamic religious education subjects at SDN Tambakrejo. The method used in this research is observational research with a qualitative data approach, the research used uses a process of data collection, observation, interviews. Needs analysis questionnaire, teaching, data collection, documentation. The number of class IV who chose the Agree (S) statement point option was 195, involving all class IV students as many as 35 students, but only 26 students were able to attend and fill out the questionnaire out of a total of 35. The conclusion from the results of this research is that students' learning motivation has increased since the introduction of a method that encourages their enthusiasm for the learning being delivered. This can be proven from the results of the motivation questionnaire which was filled out by each class IV student himself